Bydgoszcz universities students’ awareness about melanoma - Mirończuk, Katarzyna; Kałużna, Lucyna; Łakomski, Mateusz; Zukow, Walery (Journal of Education, Health and Sport, 2017)
Introduction: Malignant melanoma is a type of cancer that starts in the melanocytes. Due to the continuous increase in melanoma incidence rates public awareness of this problem is of utmost importance. There have been numerous campaigns organised in the media, on the Internet, in the press, on the radio and in dermatological clinics in order to boost overall awareness of the disease. Study objective: The analysis of the state of knowledge about the disease among the students of Bydgoszcz universities. Materials and methods: The study was conducted between the 4th of April 2016 and the 20th of May 2016 among the Bydgoszcz universities’ students of faculties of cosmetology, physiotherapy, medicine, biotechnology, pedagogy and zootechnics. A special survey form was created and used in the study. Results and conclusions:The analysis of the results showed that students of Bydgoszcz universities had good knowledge about melanoma. The study demonstrated that the level of awareness depended on the type of the university they attended. The reason for this is that at the UTP University of Science and Technology (zootechnics), the Kazimierz Wielki University (pedagogy) and the non-public University of Bydgoszcz (pedagogy) information related to medicine is not discussed. In case of most of the questions, the medical university students (Collegium Medicum) were more knowledgeable about melanoma than the students of non-medical universities. The students of cosmetology and medicine were providing most information in the survey. The respondents were able to identify melanoma risk factors and reach a conclusion that using sunbeds can pose a health hazard. Most students use sunscreens with high SPF factors, but are not aware that they need to use them at all times of the day and of the year due to the fact that harmful UV radiation is emitted with varying intensity, but constantly.